2022
DOI: 10.26668/businessreview/2022.v7i4.e453
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Open-Book Management on Customer Satisfaction: the Mediating Role of Trust

Abstract: Purpose: the current study is to test the impact of open-book management on customer satisfaction through the mediating role of trust in the hotel and tourism sector in Jordan from the perspective of customers.   Design/methodology/ approach: The study deployed the descriptive method to describe the study sample and the analytical approach to test the study hypotheses. Furthermore, the study population comprises the hotel and tourism sector in Jordan that is indexed on the Amman stock exchange (2022) which amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A positive brand sensescape can also impact consumer intentions to repurchase the product, ultimately leading to changes in consumer behavior. Previous studies documented evidence that brand experience (i.e., sensescape) has a positive impact on customer satisfaction and repurchase intention (Al Haraisa, 2022;Moreira et al, 2017;Toding & Mandagi;. The results indicated that customers who had a positive brand sensescape were more likely to be satisfied with the brand and more likely to repurchase the product.…”
Section: Hypothesis Developmentmentioning
confidence: 89%
“…A positive brand sensescape can also impact consumer intentions to repurchase the product, ultimately leading to changes in consumer behavior. Previous studies documented evidence that brand experience (i.e., sensescape) has a positive impact on customer satisfaction and repurchase intention (Al Haraisa, 2022;Moreira et al, 2017;Toding & Mandagi;. The results indicated that customers who had a positive brand sensescape were more likely to be satisfied with the brand and more likely to repurchase the product.…”
Section: Hypothesis Developmentmentioning
confidence: 89%
“…Therefore, customer satisfaction can act as a mediator connecting service quality to customer loyalty (Fernandes & Solimun, 2018). Therefore, the seventh hypothesis of this study is: H7: customer satisfaction mediates the effect between e-service quality and customer loyalty on inDrive application users in Indonesia Customers are the main indicator that must be prioritized for every business, and one way is through marketing activities (Haraisa, 2022), and customer trust is important to maintain because it has an impact on the continuity of the company's interpersonal relationships with Putra, W. P., Hendayani, R., Hidayah, R. T. (2023) Ipma's Analysis on Factors Affecting Indrive Indonesia's Customer Loyalty customers. Trusts is something that is seen by the company as an important tool in every industry, because everything is developed through consumer interaction with other people (Setiawan & Sayuti, 2017).…”
Section: Hypothesismentioning
confidence: 98%
“…They then examined the correlation between recommendation, consumer satisfaction, online shopping experience, and trust. Making decisions while shopping online is popular because it undoubtedly has the recommendations, consumer satisfaction, online shopping experience, and trust needed to make wise decisions (Haraisa, Y. E. A. 2022).…”
Section: Trustmentioning
confidence: 99%
“…intentions and concerns(Haraisa, Y. E. A. 2022)Thus, trust plays a pivotal role in the decision-making process of online shopping, and it is essential for an e-seller to establish trust with their consumers in order to ensure high consumer satisfaction and a greater likelihood of a recommendation (MA & YAO, 2013) .…”
mentioning
confidence: 99%